Addressing the unique healthcare needs of women: Opportunity for change exists at the intersection of precision health and learning health systems. Issue 2 (21st July 2017) - Satveit, Sonya
Abstract: Introduction: Women have unique healthcare needs that are not well addressed by our current healthcare system and with healthcare transformation underway the opportunity exists to avoid weaving these age‐old problems into the fabric of the new healthcare design. myAva is an example of a learning health system integrated into a cloud‐based precision health platform. The goal of myAva is to integrate the tools of precision health and principals of a learning health system to improve care for women, starting with polycystic ovary syndrome (PCOS). Methods: Putting patients at the center in designing a new style of healthcare has been an important concept underlying the development of myAva since inception. Understanding the needs of patients and providers is key to the development of myAva. Surveys were collected from members of the PCOS patient community and patient and medical advisory boards were recruited. For the pilot group comprehensive omic data, biometric and self‐reported data were collected and integrated into a personalized health dashboard enabling providers to formulate personalized treatment plans. The ongoing collection of data will create continuous improvement of healthcare. Results: Precision health for chronic issues faced is in its infancy and although myriad challenges exist the potential to improve health outcomes is great. myAva's providers, patients, and advisors are encouraged by the early outcomes of the program with improved health outcomes and an increased sense of empowerment reported. It is clear that designing and implementing this type of care requires collaboration, the involvement of all stakeholders, with patients at the center.